(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article analyzes the theoretical and practical foundations for implementing innovative approaches in the teaching of mathematics. The growing influx of information and the necessity for adaptive responses demand the formation of innovative competencies in modern pedagogical practice. The authors examine various scholarly views on innovation and justify the role, essence, and stages of applying innovative technologies in pedagogical activities. Moreover, the article explores the concept of modernization in both social and educational contexts, highlighting its intrinsic connection to transformations in the education sector. As a result, the authors propose scientific and practical recommendations aimed at enhancing the effectiveness of the educational process through innovative approaches.